Orient-Occident : Origines mythiques d’un couple réel - Hentsch, Thierry (Études internationales, 1985)
What the United Nations brought to the International Community during its forty years of life cannot be assessed only by referring to the working of the institution and the success or failures it encountered in dealing with specific questions or crises. The profound and lasting changes in the International Community itself in which it contributed in bringing about must also be taken into consideration. Undoubtedly, the most considerable of these changes, a mutation, in the real sense of the word, was the passage from an international society centered around Europe and North-America in 1945, to a truly world society in 1985, through the process of decolonisation. The United Nations decisively contributed to the spreading of the ideology of decolonisation, to the enactment of an international law of decolonisation and to the use of multilateral diplomacy against colonial powers. Eventually, admission to the United Nations became the visible sign as well as the final step of the attainment of political independence. Another remarkable new feature of the international society of today, closely related to the preceding one, is the importance of groups of states, like the Seventy Seven and the Non Aligned, acting as pressure groups. This new setting was made possible only with the existence of the United Nations, where "group diplomacy" was able to deploy itself and to make the "power of the number" felt. Eventually, the whole present diplomatic game, which is played at the level of the world rather than on a bilateral or regional basis in an always growing number of fields, is a product of development of multilateral diplomacy within the United Nations. It is specially true of the so-called North-South dialogue - or confrontation. The World Organization is now an irreversible fact of international life and a reflection of the present structure of the International Society that it helped to build up. But on the other hand, it is a very novel experiment in a historical perspective. Much is y et to be learned in order to be able to make the best use of the instruments it affords for managing the world community.